The Influence of Digipos Aja Application Product Quality, Price, and Promotion on Customer Satisfaction in Makassar City - Ismu Widodo; Edi Witjara; Siska Noviarisanti; Muhammad Luthfi Siraj (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2023)
Digipos Aja Telkomsel, in carrying out digital transformation, also makes innovations in the digital world, one of which is creating Digipos Aja. Based on Telkomsel's internal data for 2021, there are 532,538 Digipos Aja Telkomsel registrations. This study explores Digipos Aja application product quality, prices, and promotions impact on consumer satisfaction in Makassar City. Methodology, This study employs correlational research that utilizes statistical correlations to describe and measure the relationship between two or more variables with multiple regression method. Finding: This study suggests that all variables have valid values. While the results of hypothesis testing show that partially each variable has a significant influence and simultaneously the variable quality of the Digipos Aja application product, price, and promotion on consumer satisfaction in Makassar City. Which means that the three X variables have a significant influence to variable Y. Conclusion: Product quality, price, and promotion simultaneously affects consumer satisfaction in Makassar City and all of them are statistically significant. The higher quality level of Digipos Aja product subsequently elevate consumer confidence level towards the product. Additionally, with high level of trust for Digipos Aja products, therefore consumers are able to select and create purchasing decisions for these products.